Estudo cromossômico em aranhas diminutas, incluindo os primeiros registros para as famílias Palpimanidae e Theridiosomatidae (Araneae, Araneomorphae) - DÉBORA DUARTE DUTRA (2022)
Spiders are amongst the most diverse animal groups in the world, with 49.938 species distributed in 131 families. Despite the great diversity, only 835 species (1,6%) have chromosomal data available in the literature. This scarcity of cytogenetic data makes it difficult to discuss chromosomal evolution in most groups of this order, including tiny spider families such as Oonopidae and Theridiosomatidae. The aim of this work was to chromosomally analyze spiders smaller than one centimeter in length, with the aim of contributing to the discussion on the cytotaxonomy and/or chromosomal evolution of the groups. The collections were carried out in Mato Grosso do Sul and by active nocturnal search, in the case of Theridiosomatidae, and by sieving litter, with manual screening of the sieved for the other representatives. In most cases, due to the small size, the entire animal was subjected to colchicine treatment (0,16%, 2h), hypotonic (tap water, 15 min) and fixation in Carnoy I (methanol:acetic acid 3:1, minimum 1h) with the contents of the abdomen partially exposed to facilitate the action of reagents.The slides were prepared with the total content of the abdomen, except for individuals of Epicratinus sp. and Falconina sp. in which the use only of the gonads was possible, and were later stained with Giemsa (3%, 15 min). Altogether 12 species belonging to eight families were analyzed. The results were 2n♀=36 for Otiothops birabeni (Palpimanidae), 2n♂=30, X1X2 for Naatlo sp. (Theridiosomatidae), 2n♂=24, X1X2 in Agyneta sp. (Linyphiidae), 2n♂=22, X1X2 for Coleosoma floridanum, Thymoites sp.1 and Thymoites sp.2 (Theridiidae), 2n♂=28, X1X2 for Falconina sp. (Corinnidae), 2n♂=21, X for Orthobula sp. (Trachelidae), 2n♂=42, X1X2 for Epicratinus sp. (Zodariidae), 2n♂=9, X for Cinetomorpha simplex (Oonopidae), and 2n♂=7, X for Neotrops sp. and Neoxyphinus termitophilus (Oonopidae). The chromosome morphology in most species was telocentric, but chromosomes with two arms were also found. The obtained results contributed to the knowledge about the karyotypic evolution in poor studied groups of Araneomorphae, providing the first records for whole families, as in the case of Palpimanidae and Theridiosomatidae. The relatively high chromosome number found in O. birabeni (2n♀=36) (Palpimanidae, nonentelegyne) agrees with the ancestral karyotype proposed for Entelegynae. The results of Naatlo sp. (2n♂=30, X1X2) revealed an unrecorded diploid number for the superfamily Araneoidea, as well as the rarely recorded presence of two-armed chromosomes. The data obtained in Agyneta sp., C. floridanum, Thymoites sp.1 and Thymoites sp.2 showed the same pattern already described for most of the karyotyped species in Linyphiidae (2n♂=24, X1X2) and Theridiidae (2n♂= 22, X1X2). The diploid number found in Falconina sp. (2n♂=28) chromosomally distinguishes to date the subfamily Castianeirinae from the subfamily Corinninae. The chromosomal data of Orthobula sp. (2n♂=21, X) differ from those found for the other species of Trachelidae already analyzed, agreeing with recently proposed phylogenies. The result found in Epicratinus sp. (2n♂=42, X1X2) was similar in diploid number and Sexual Chromosome System to those already reported for Pax islamita, which belongs to a distinct subfamily and geographic region, suggesting that this karyotype is ancestral to Zodariidae. The karyotype found in Neotrops sp. and N. termitophilus (2n♂=7, X) is probably the ancestor for Oonopidae, while the karyotype data of C. simplex (2n♂=9, X) was a particular case in relation to the other analyzed species of the family and can be considered a possible synapomorphy for the genus.